2017
DOI: 10.1371/journal.pone.0170086
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Level and Cardiac Autonomic Modulations in Coronary Artery Disease and Cardiac Syndrome X Patients

Abstract: BackgroundAnxiety and cardiac autonomic modulations (CAM) were thoroughly investigated in coronary artery disease (CAD) and cardiac syndrome X (CSX) patients worldwide, but not among Sudanese with similar pathology.AimsTo compare levels of anxiety and CAM between Sudanese patients with CSX and CAD.Materials and MethodsAnxiety was evaluated in 51 CAD and 26 CSX patients using Taylor Manifest anxiety score (TMAS) questionnaire while heart rate variability derived indices were used to assess CAM, namely natural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some researchers and cardiologists consider atypical chest pain as subclinical manifestation of CVD when associated with positive stress test 27 . The patients from the NCCP group, took medications prescribed by a cardiologist (betablockers, acetylsalicylic acid), despite the fact that CVD was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers and cardiologists consider atypical chest pain as subclinical manifestation of CVD when associated with positive stress test 27 . The patients from the NCCP group, took medications prescribed by a cardiologist (betablockers, acetylsalicylic acid), despite the fact that CVD was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…CSX patients reported more depression, anxiety, and somatic concerns than patients with confirmed coronary disease [23]. In contrast to Lutfi’s study [24], which demonstrated that the Taylor Manifest anxiety score questionnaire 35 failed to show significant association with CSX, Asbury et al [25] observed that CSX patients showed more life interference and higher HADS anxiety scores than CHD patients, and CSX and CHD patients both had higher depression scores than the healthy controls [24, 25]. Consistent with the literature, in this study, CSX patients had much higher anxiety and depression scores than the healthy controls ( p < 0.001, p = 0.003 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a decreased tolerance for cardiac pain may be the pathophysiological background for NOCAD. In addition, these patients are much more likely to suffer from anxiety and panic disorders, which could be responsible for angina-like symptoms [ 21 , 22 ]. Moreover, the hypersensitivity to right atrial pressure and volume alterations may play a role as well [ 23 ].…”
Section: Introductionmentioning
confidence: 99%